EFFICIENCY OF PUBLIC-PRIVATE PARTNERSHIP IN REFORMING THE HEALTH CARE SYSTEM: GLOBAL EXPERIENCE AND PROSPECTS FOR UKRAINE - Вашев, Олег; Хижняк, Станіслав (SWorldJournal, 2024)
The article examines the role of public-private partnership (PPP) as a tool for reforming the health care system using the example of world experience and its potential for Ukraine. The main models of interaction between the public and private sectors, w